2018
DOI: 10.1016/j.bbmt.2018.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus-6B Reactivation Is a Risk Factor for Grades II to IV Acute Graft-versus-Host Disease after Hematopoietic Stem Cell Transplantation: A Systematic Review and Meta-Analysis

Abstract: Graft-versus-host disease (GVHD) is an important cause of morbidity and mortality after allogeneic hematopoietic cell transplantation (HCT). Many studies have suggested that human herpesvirus-6B (HHV-6B) plays a role in acute GVHD (aGVHD) after HCT. Our objective was to systematically summarize and analyze evidence regarding HHV-6B reactivation and development of aGVHD. PubMed and EMBASE databases were searched using terms for HHV-6, HCT, and aGVHD, yielding 865 unique results. Case reports, reviews, articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 86 publications
2
47
1
Order By: Relevance
“…Most studies of these two conditions in HSCT patients have been carried out in adults and mixed populations (adults and children). [5][6][7]9,11,14,16,17,19,20,22,24,32,33 In pediatric HSCT patients, several studies have been conducted to elucidate Bold values are statistically significant. were risk factors for HHV-6B infection after transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of these two conditions in HSCT patients have been carried out in adults and mixed populations (adults and children). [5][6][7]9,11,14,16,17,19,20,22,24,32,33 In pediatric HSCT patients, several studies have been conducted to elucidate Bold values are statistically significant. were risk factors for HHV-6B infection after transplant.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Although the frequency and timing of HHV-6B infection after HSCT is clear, the nature of the association between HHV-6B infection and clinical manifestations in HSCT patients is still a matter of debate. It has been suggested that viral infection is associated with fever, 2,8 acute graft-versus-host disease (GVHD), 6,[8][9][10][11][12] engraftment delay, 6,13 and post-transplant acute limbic encephalitis (PALE). [14][15][16][17][18][19][20] Of these clinical manifestations, the strongest causal relationship has been demonstrated between viral infection and PALE.…”
Section: Introductionmentioning
confidence: 99%
“…HHV-6B is a highly prevalent beta-herpes virus, infecting about 90% of the individuals in many Western populations [1]. The occurrence of episodes of viral reactivation observed in immunosuppressed individuals such as transplant patients and human immunodeficiency virus (HIV)-1-infected individuals [5][6][7][8][9]. Both CD4 and CD8 T cells responding to HHV-6B have been observed [10][11][12][13], although a full understanding of the role of the different subsets in controlling the infection is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the underlying mechanisms of viral integration remains poorly understood. Although previous studies have observed HHV-6A/B reactivation inducing diseases in patients [67][68][69][70], reactivation of the virus genome in vitro is challenging. In most cell lines, induction of reactivation using various reagents only results in the expression of some viral genes without the production of viral particles [55,71,72].…”
Section: Introduction: Herpesvirusesmentioning
confidence: 99%